2014
DOI: 10.1126/science.1257158
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-driven unimolecular reaction of CH 3 CHOO Criegee intermediates to OH radical products

Abstract: Ozonolysis of alkenes, an important nonphotolytic source of hydroxyl (OH) radicals in the troposphere, proceeds through energized Criegee intermediates that undergo unimolecular decay to produce OH radicals. Here, we used infrared (IR) activation of cold CH3CHOO Criegee intermediates to drive hydrogen transfer from the methyl group to the terminal oxygen, followed by dissociation to OH radicals. State-selective excitation of CH3CHOO in the CH stretch overtone region combined with sensitive OH detection reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(168 citation statements)
references
References 29 publications
9
150
0
3
Order By: Relevance
“…After the discovery of this source of CH 2 OO, many researchers utilized this scheme to produce CH 2 OO and reported ultraviolet (UV) depletion, 18 UV absorption, 19,20 infrared (IR) absorption, 21 microwave, 22,23 and submillimeter-wave 24 spectra. Spectra of slightly larger Criegee intermediates such as acetaldehyde oxide (CH 3 CHOO), 15,[25][26][27][28][29][30][31][32] acetone oxide [(CH 3 ) 2 COO], 16,33 and propionaldehyde oxide (C 2 H 5 CHOO) 10 are also reported. Figure 1 shows the structures of CH 2 OO, syn-CH 3 CHOO, and anti-CH 3 CHOO.…”
Section: Spectroscopy Of Criegee Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the discovery of this source of CH 2 OO, many researchers utilized this scheme to produce CH 2 OO and reported ultraviolet (UV) depletion, 18 UV absorption, 19,20 infrared (IR) absorption, 21 microwave, 22,23 and submillimeter-wave 24 spectra. Spectra of slightly larger Criegee intermediates such as acetaldehyde oxide (CH 3 CHOO), 15,[25][26][27][28][29][30][31][32] acetone oxide [(CH 3 ) 2 COO], 16,33 and propionaldehyde oxide (C 2 H 5 CHOO) 10 are also reported. Figure 1 shows the structures of CH 2 OO, syn-CH 3 CHOO, and anti-CH 3 CHOO.…”
Section: Spectroscopy Of Criegee Intermediatesmentioning
confidence: 99%
“…For an initial temperature of 300 K, beginning from the transition state of CH 2 OO, the system reaches the dioxirane structure in ∼50 fs, then isomerizes to formic acid (in ∼2.8 ps) that decomposes readily into H 2 O + CO. 88 The hydrogen transfer of CH 2 ), 28,91 so that irradiation of CH 3 CHOO with IR light (>5603 cm −1 ) to excite its CH-stretching overtone produces OH (and vinoxy radical CH 2 CHO). 28 Kumar et al found that carboxylic acids catalyze the isomerization reaction to such an extent that it becomes a barrierless process. 92 In contrast, water produces only a nominal catalytic effect.…”
Section: A Stabilization Vs Decompositionmentioning
confidence: 99%
“…However, direct detection of CIs only became feasible after Welz et al 2 produced CIs efficiently by the reaction of an iodoalkyl radical with O 2 : e.g., CH 2 I + O 2 → CH 2 OO + I. According to recent studies, [3][4][5] CIs play an important role in atmospheric chemistry, being responsible for the oxidation of SO 2 , NO 2 , organic and inorganic acids, alkenes, and water vapor, 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] the formation of OH radicals [20][21][22][23] and aerosols. Furthermore, significant structure-dependent chemistry of CIs has also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…7 Because SCIs are readily consumed, they have very low steady-state concentrations, 8 and consequently their fate in the atmosphere is not well established. 1 To provide a relatively clean source of SCIs for spectroscopic, 9-21 dynamics, [22][23][24][25][26] and kinetics studies, [27][28][29][30][31][32][33][34][35][36] SCIs are almost exclusively made from photo-oxidation reactions of (R 1 R 2 )CI 2 in the presence of O 2 (where R 1 /R 2 represent hydrogen atoms or alkyl radicals To provide accurate rate constants and to aid experimental measurements, unimolecular decomposition rate constants of syn-CH 3 CHOO under atmospheric conditions are computed here from first principles using Miller's semiclassical transition state theory (SCTST) [41][42][43][44][45] in combination with a two-dimensional master equation (2DME) approach. 7,46 This chemical kinetics analysis is performed using a high accuracy potential energy surface that is constructed with a modification of the HEAT protocol.…”
Section: Introductionmentioning
confidence: 99%